1997
DOI: 10.1126/science.278.5339.866
|View full text |Cite
|
Sign up to set email alerts
|

IκB Kinase-β: NF-κB Activation and Complex Formation with IκB Kinase-α and NIK

Abstract: Activation of the transcription factor nuclear factor kappa B (NF-kappaB) by inflammatory cytokines requires the successive action of NF-kappaB-inducing kinase (NIK) and IkappaB kinase-alpha (IKK-alpha). A widely expressed protein kinase was identified that is 52 percent identical to IKK-alpha. IkappaB kinase-beta (IKK-beta) activated NF-kappaB when overexpressed and phosphorylated serine residues 32 and 36 of IkappaB-alpha and serines 19 and 23 of IkappaB-beta. The activity of IKK-beta was stimulated by tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
846
1
3

Year Published

1998
1998
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,128 publications
(878 citation statements)
references
References 16 publications
28
846
1
3
Order By: Relevance
“…TRAF2 and its homologs have been recently shown to bind to NIK, which subsequently binds to two recently identi®ed protein kinases termed I-kappa B kinase kinase 1 (IKK1 or IKKa) and 2 (IKK2 or IKKb) (Figure 1) (DiDonato et al, 1997;Mercurio et al, 1997;Regnier et al, 1997;Woronicz et al, 1997;Zandi et al, 1997). As shown in Figure 3c, dominantnegative mutants of NIK and IKK2 could block NFkB activation mediated by the ORF-K13, whereas a similar mutant of IKK1 failed to do so.…”
Section: Mechanism Of Orf-k13-induced Nf-kb Activationmentioning
confidence: 93%
“…TRAF2 and its homologs have been recently shown to bind to NIK, which subsequently binds to two recently identi®ed protein kinases termed I-kappa B kinase kinase 1 (IKK1 or IKKa) and 2 (IKK2 or IKKb) (Figure 1) (DiDonato et al, 1997;Mercurio et al, 1997;Regnier et al, 1997;Woronicz et al, 1997;Zandi et al, 1997). As shown in Figure 3c, dominantnegative mutants of NIK and IKK2 could block NFkB activation mediated by the ORF-K13, whereas a similar mutant of IKK1 failed to do so.…”
Section: Mechanism Of Orf-k13-induced Nf-kb Activationmentioning
confidence: 93%
“…Specifically, dominant-negative forms of IKKa and b, which are capable of blocking activation of NF-kB, can be created either by mutations in the ATP-binding site or by mutations in the kinase activation loop (DiDonato et al, 1997;Mercurio et al, 1997;Regnier et al, 1997;Woronicz et al, 1997;Zandi et al, 1997;Ling et al, 1998). Because of their distinct roles in the canonical (IKKb-dependent) and non-canonical (IKKa-dependent) pathways, dominantnegative IKK mutants can show stimulus-dependent inhibition.…”
Section: Inhibitors Of Ikk Complex Activitiesmentioning
confidence: 99%
“…36 Previous studies indicated that members of the mitogenactivated protein kinase kinase kinase protein kinase family mediate physiologic activation of IKK. 37 These kinases include NIK 38 and mitogen-activated protein kinase/extracellular signal-regulated kinase kinase 1. 39 Dominant interfering mutants of IkBa and IkBb and kinase-deficient mutants of IKKa, IKKb and NIK were tested for their ability to inhibit Tax-mediated activation of survivin-driven reporter gene.…”
Section: Tax Transactivation Of Survivin Promotermentioning
confidence: 99%